Asynchronous rhythms of circulating conjugated and unconjugated bile acids in the modulation of human metabolism. (31st July 2018) - Al‐Khaifi, A.; Straniero, S.; Voronova, V.; Chernikova, D.; Sokolov, V.; Kumar, C.; Angelin, B.; Rudling, M.
Abstract: Background and Objectives: Bile acids (BAs) traversing the enterohepatic circulation (EHC) influence important metabolic pathways. By determining individual serum BAs in relation to markers of metabolic activity, we explored how diurnal variations in their EHC relate to hepatic metabolism in normal humans. Methods: Serum BAs, fibroblast growth factor 19 (FGF19), lipoproteins, glucose/insulin and markers of cholesterol and BA syntheses were monitored for 32 h in 8 healthy males. Studies were conducted at basal state and during initiation of cholestyramine treatment, with and without atorvastatin pretreatment. Time series cross‐correlation analysis, Bayesian structural model and Granger causality test were applied. Results: Bile acids synthesis dominated daytime, and cholesterol production at night. Conjugated BAs peaked after food intake, with subsequent FGF19 elevations. BA synthesis was reduced following conjugated BA and FGF19 peaks. Cholestyramine reduced conjugated BAs and FGF19, and increased BA and cholesterol production; the latter effects attenuated by atorvastatin. The relative importance of FGF19 vs. conjugated BAs in this feedback inhibition could not be discriminated. Unconjugated BAs displayed one major peak late at night/early morning that was unrelated to FGF19 and BA synthesis, and abolished by cholestyramine. The normal suppression of serum triglycerides, glucose and insulin observed at night was attenuated by cholestyramine. Conclusions: Conjugated and unconjugated BAs have asynchronous rhythms of EHC in humans. Postprandial transintestinal flux of conjugated BAs increases circulating FGF19 levels and suppresses BA synthesis. Unconjugated BAs peak late at night, indicating a non‐postprandial diurnal change in human gut microflora, the physiological implications of which warrants further study.